Attributes of Urban Green Infrastructure (UGI) and its use by young adults in Kuala Lumpur City - Mansor, Mazlina; Harun, Nor Zalina; Zakariya, Khalilah (e-International Publishing House, Limited, 2020)
Attachment to indoor activities has implications for young people in a city, such as sedentary behaviour. It may be the cause of the rise of non-communicable diseases (NCDs). Nature in a city, i.e. Urban Green Infrastructure (UGI) is vital to overcome these issues. It acts as a reinforcement to promote healthy lifestyles. The study explores young people’s use and favourable attributes that attract them to UGI. A survey of young people (n=1397) was conducted in Kuala Lumpur and Putrajaya. Safety, nature, cleanliness and design aspects are the attributes that UGI needs to reduce the sedentary indoor lifestyle of young people.